Photoaffinity labeling the nucleotide sites of the sarcoplasmic reticulum Ca²⁺-ATPase - Seebregts, Christopher J (Division of Chemical Pathology, 2018)
We have synthesized a new class of photoaffinity analogs, 2',3'-O-(2,4,6-trinitrophenyl)-8-azido-ATP, -ADP and -AMP (TNP- 8N₃ATP, -ADP and -AMP), and their radiolabeled derivatives, and characterized their interaction with the sarcoplasmic reticulum Ca²⁺-ATPase. The TNP-8N₃-nucleotides were synthesized from ATP in three steps involving bromination in the 8-position of the adenine ring followed by displacement with an azido group and then trinitrophenylation of the resulting 8N₃-nucleotide with TNBS. Inclusion of the oxidizing agent, DTNB, in the final reaction was found to be necessary to prevent reduction of the azido group by the released sulfite anion and also elevated the yield of trinitrophenylation to about 80%. Purity was determined spectrophotometrically, as well as by anion exchange TLC and reversed phase HPLC. In the dark, the compounds were found to display most of the features of the parent TNP-nucleotides and interacted with the Ca²⁺-ATPase in a similar way. When activated by illumination, the probes were specifically incorporated into SR vesicles with high efficiency at alkaline pH. The site of labeling was identified as being on the A₁ tryptic fragment.